PENINGKATAN KETERAMPILAN MENULIS TEKS PIDATO DENGAN PEMETAAN PIKIRAN (MIND MAPPING) SISWA KELAS VI SD NEGERI 006 KECAMATAN RAMBAH KABUPATEN ROHUL - Nisdawati Nisdawati (JURNAL PENDIDIKAN ROKANIA, 2017)
This research was conducted to obtain a description of the process of improving the skill of writing text to speech with mind mapping Elementary School sixth grade students Rambah 006. The method used was classroom action research conducted in two cycles. Each cycle consists of four stages of research, including planning, implementation, observation, and reflection. This research data is the result of observation of the actions of teachers and students in learning, fieldnotes and student learning outcomes. Data from teacher activity observation and field notes were analyzed qualitatively. Data from learning to write text to speech and the observation of student activities were analyzed quantitatively. The results showed that mind mapping is used as a tool in learning can enhance the activity and student learning outcomes in writing the text of the speech. The learning process with the help of mind mapping to help students generate ideas and ideas principal explanatory, and connecting those ideas into coherent sentences and coherently. Thus, learning to write text to speech using mind mapping to make students think critically, logically and systematically. Meanwhile, the factors that impede learning to write text to speech with the help of mind mapping is not maximized classroom management and a lack of mastery of student’s vocabulary.